A Single-Center Case Series of Hereditary Ataxia from Gujarat: Clinical and Genetic Data (GAIMS Journal of Medical Sciences, 2025)
Background: Hereditary or genetic ataxia is a group of neurodegenerative conditions, characterized by progressive imbalance and ataxia, with convergent clinical profiles. Limited data on the prevalence and subtypes are available from Gujarat due to a lack of an ataxia registry or studies.Objective: To study clinical and genetic characteristics in patients with hereditary ataxia from Gujarat state.Material and Methods: This prospective observational study included and evaluated chronic cerebellar ataxia patients with suspected hereditary etiology. Based on the clinical findings, molecular analysis was performed using PCR-based trinucleotide repeat analysis for a single specific genotype, a selected panel, or a broader whole-exome sequencing method.Results: We identified 65 patients with possible genetic ataxia over 2 years. Forty-nine patients from this subgroup underwent genetic testing and obtained positive results in 29 patients. Spinocerebellar ataxia (SCA) type 2 was the most common type (31%) of Autosomal Dominant ataxia, and Friedreich’s ataxia (FA) was the most common Autosomal Recessive ataxia (13.8%). SCA patients had onset in the 2nd decade onwards and had strong positive family history, while FA patients had onset in the 1st decade. Clinical features were overlapping and nonspecific for the subtype of ataxia. Apart from incoordination, the most common clinical findings were eye signs, pyramidal tract involvement and peripheral neuropathy.Conclusion: Our Gujarat state cohort of hereditary ataxia resembles genotypic and clinical characteristic data from other studies in western India. We noted clinical phenotypic overlap in all subtypes of hereditary ataxia, which calls for molecular genetic testing for diagnosis.